Reflections on the (bio)ethical aspects of conversion therapies for sexual orientation (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The paper aims to reflect on the most recent psychoanalytically-based sexual orientation conversion therapies and their compatibility with the ethical standards of the profession. After outlining the most important guidelines on the subject, the article delves into so-called reparative therapies and, subsequently, identity conversion therapies, to then assess whether and how they comply with the principles of beneficence, autonomy, and non-discrimination.
Keywords: SOCE; sexual orientation; affirmative approaches; conversion therapy